A classroom experiment on the specific factors model. (June 2021) - Lin, Yu-Hsuan
Abstract: This paper proposes a classroom experiment to illustrate the specific-factors model. In it, students act as decision-makers in an economy comprising two goods and three factors, and each is asked to maximize the value of marginal production by allocating his/her labor force between the two sectors. Through trading products, all players work as a whole economy in pursuit of higher welfare. From their individual perspectives, they can observe the impacts of relative price changes and international labor mobility on productivity and income distribution. The group perspective, meanwhile, reveals the gains arising from trade and welfare. Together with discussion of theoretical predictions, experimental results and case studies, this classroom experiment could foster better learner understanding of the specific-factors model, both individually and collectively.